"AS IF I WERE AN ILLEGAL": Racial Passing in Immigrant Russia. (12th December 2022) - WOODARD, LAUREN
ABSTRACT: This article examines how immigrants from post‐Soviet countries engage in practices of racial passing to challenge ethnic stereotypes in Russia, the world's fourth‐largest migration destination. Ethnographic research reveals that immigrants shed signs of illegality to pass not necessarily as white, ethnic Russians (russkie) but instead as ethnically heterogeneous Russian citizens (rossiiane) . The need to pass points to fundamental tensions within Russian society about belonging, tensions arising from a particular configuration of race, ethnicity, and language that emerged during the Soviet era. I show how ethnic Russianness operates akin to whiteness, the invisible ideal against which racialized bodies are marked, despite Soviet‐era anti‐racism campaigns and contemporary claims of Russia's multiethnic diversity. This article contributes to scholarship analyzing migration and citizenship as racial projects by demonstrating how locally nuanced inflections of whiteness interact with global and transnational movements of white supremacy. РЕЗЮМЕ: В этой статье исследуется то, как иммигранты из постсоветских стран вовлечены в практики расового пассинга, усложняющие этнические стереотипы в России (занимающей четвертое место в мире по величине миграционного притока). Этнографическое исследование показывает, что иммигранты скрывают маркеры нелегальности, чтобы выдать себя не обязательно за белых этнических русских, а вместо этого за этнически неоднородных российских граждан (россияне). Необходимость такого пассинга указывает на фундаментальную напряженность в российском обществе относительно самоидентификации, которая возникает из‐за особой конфигурации расы, этничности и языка, возникшей в советское время. Я показываю, как этническая 'русскость' действует подобно белизне, невидимому идеалу, рядом с которым существуют расиализированные тела, на фоне антирасистских кампаний советской эпохи и современных заявлений о многонациональности России. Эта статья вносит вклад в исследования, которые анализируют миграцию и гражданство как расовые проекты, демонстрируя, как локальные нюансы белизны взаимодействуют с глобальными и транснациональными движениями за превосходство белых.